Perbandingan Administrasi Negara Indonesia Dengan Korea Selatan - Nur Wahyuni (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
The term "comparison" in the Science of Comparative State Administration contains the meaning of juxtaposing and drawing terms of similarities and/or differences from symptoms, phenomena, or goals. Administration, in its sense, is one of the symptoms of life in society in which a group of people or citizens act to realize or achieve certain goals. Research is carried out using library research, so the method used in research is literature study. The focus of this research is on comparing Indonesia's bureaucracy and state administration system with those of North Korea. The technique used in collecting data in this study uses secondary data. Data analysis used descriptive and qualitative analysis through a literature study. The results of the study show that the aspects being compared are the Indonesian bureaucratic system and state administration system with South Korea. A comparison of the bureaucratic systems in Indonesia and South Korea includes bureaucracy based on groups and bureaucratic management. And a comparison of the administrative systems in Indonesia and South Korea based on the country's culture, including the presidential system, legal system, financial administration system, and regional government system.